A BOOK REVIEW: GRAPmc NOVELS: A FUN & CREATIVE WAY OF WRITING AND READING - Ekawati Marhaenny Dukut (Celt: A Journal of Culture, English Language Teaching & Literature, 2010)
The 21" century is marked for the vast development of digital media. I fbefore, communicating with people from another country is reached by the sending ofletters or making international phone calls, nowadays people can do all of those in one go with the internet. Whether it is writing to people or speaking to them, all can be done at once with a bonus of even seeing who and what the other end is doing. The chatting facilities of e.g. the Yahoo Messenger or Skype make it possible. Similarly, ifbefore students would spend hours of research at a library to fmd and read books, nowadays some of those same books can be read digitally in their own homes. Yet, Nancy Frey exclaims: "Readers in the 21 st century need to be able to analyze what they read and understand the motive of the author and the accuracy of the reading. They need to see themselves as active users, not merely vessels to be filled" (in http://www.educationworld.com /a_curr/profdev/profdevl05.sht m1, 2010). To do this, the traditional method of giving books to students to read either inside or outside the classroom, is a fact not to be argued. The problem is, with numerous instant facilities that a student can have now, may make them not patient enough to sit for long hours reading the pages and pages of books assigned by a teacher.